Second Language Experience Facilitates Sentence Recognition in Temporally-Modulated Noise for Non-native Listeners - Guan, Jingjing; Cao, Xuetong; Liu, Chang (Frontiers in Psychology, 2021)
Non-native listeners deal with adverse listening conditions in their everyone lives much harder than native listeners. However, previous work in our laboratories found that native Chinese listeners with native English exposure may improve the use of temporal fluctuations of noise for English vowel identification. The purpose of this study was to investigate whether Chinese listeners can generalize the use of temporal cues for the English sentence recognition in noise. IEEE sentence recognition in quiet condition, stationary noise, and temporally-modulated noise were measured for native American English listeners (EN), native Chinese listeners in the US (CNU), and native Chinese listeners in China (CNC). Results showed that in general, EN listeners outperformed the two groups of CN listeners in quiet and noise, while CNU listeners had better scores of sentence recognition than CNC listeners. Moreover, the native English exposure helped CNU listeners use high-level linguistic cues more effectively and take more advantage of temporal fluctuations of noise to process English sentence in severely degraded listening conditions (i.e. the SNR of -12 dB) than CNC listeners. These results suggest a significant effect of language experience on the auditory processing of both speech and noise.